2006
DOI: 10.1021/bc060039e
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Tailored Ferrocenyl Molecules as Electrochemical Probes of Biochemical Interactions

Abstract: The development of electrochemical probes useful for investigating the occupancy by other molecules of sites on complex proteins such as human serum albumin (HSA) is described. Ferrocenyl-(oxoethylene)-fatty acid compounds of different fatty acid chain length probed different binding sites on HSA. The interaction could be changed from one primarily with a drug binding site, when the probe was ferrocene methanol, to one predominantly with medium-chain fatty acid binding sites, by adding an (oxoethylene)-fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Thus, we have identified that, to enable electrochemical measurements to be made in protein solutions, plasma, and blood, an amide at linker A, carbamate at linker B, short PEG unit, and fatty acid moiety are required for use in biomolecular binding studies, to mimic fatty acid binding. Applications of the model compound 17 and analogues as an electrochemical probe of biochemical interaction will be described in a future paper (30).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we have identified that, to enable electrochemical measurements to be made in protein solutions, plasma, and blood, an amide at linker A, carbamate at linker B, short PEG unit, and fatty acid moiety are required for use in biomolecular binding studies, to mimic fatty acid binding. Applications of the model compound 17 and analogues as an electrochemical probe of biochemical interaction will be described in a future paper (30).…”
Section: Discussionmentioning
confidence: 99%
“…Research on improving the electron transfer has been focused on the mediators and conductive polymers, where Ferrocene derivatives and Prussian blue have been used as mediators [1][2][3][4][5][6]. Similar conducting polymers such as polypyrrole, polyoxane, poly(ethylene oxide), and poly(toluidine blue O) are also used as mediating conductive polymers [3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%